Strategically Organic: One U.S. History Teacher's Experience With Class Discussion. Issue 2 (1st July 2015) - Sullivan, Caroline C.; Schewe, Audrey; Juckett, Emily; Stevens, Heather
Abstract : Effective discussion is inextricably linked to democracy. Social studies curriculum and instruction should engage students in practicing democratic skills and habits of mind. This case study provides a microanalysis of one U.S. History teacher's commitment to fostering discussion in her classroom as a theorized pedagogical practice. A better understanding of what motivates teachers to engage students in classroom discussions paralleled with rich descriptions of how this teacher plans and implements discussion could encourage others to try this approach to teaching and learning.